Unexpected Power: Conflict and Change among Transnational Activists - Thomas, Mark (Labour / Le Travail, 2008)
The article reviews the book, "Unexpected Power: Conflict and Change Among Transnational Activists," by Shareen Hertel.
Keywords: BOOKS -- Reviews; Employee rights; HERTEL, Shareen; Nonfiction; UNEXPECTED Power: Conflict & Change Among Transnational Activists (Book)